Cover Picture: Dynamic Magnetic and Optical Insight into a High Performance Pentagonal Bipyramidal DyIII Single‐Ion Magnet (Chem. Eur. J. 24/2017). Issue 24 (28th February 2017) - Chen, Yan‐Cong; Liu, Jun‐Liang; Lan, Yanhua; Zhong, Zhi‐Qiang; Mansikkamäki, Akseli; Ungur, Liviu; Li, Quan‐Wen; Jia, Jian‐Hua; Chibotaru, Liviu F.; Han, Jun‐Bo; Wernsdorfer, Wolfgang; Chen, Xiao‐Ming; et al.
Abstract : The pentagonal bipyramidal single‐ion magnets (SIMs) are among the most attractive prototypes of high performance single‐molecule magnets (SMMs). A fluorescence‐active phosphine oxide ligand is introduced, and by combining dynamic magnetic measurements, optical characterization, and ab initio calculations, the magneto‐optical correlation of a high‐performance pseudo‐ D 5 h Dy III SIM with large U eff = 508(2) K and high magnetic hysteresis temperature of 19 K, [Dy(CyPh2 PO)2 (H2 O)5 ]Br3 ⋅2 (CyPh2 PO)⋅EtOH⋅3 H2 O (CyPh2 PO=cyclohexyl(diphenyl)phosphine oxide) was studied. This work provides a deeper insight into the rational design of promising molecular magnets. More information can be found in the Full Paper by M.‐L. Tong, J.‐L. Liu, et al. onpage 5708 ff.